2009
DOI: 10.1260/026361709789868884
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Adsorption of 2-Propanol onto Silica Surfaces on the Basis of Ab Initio and Density Functional Calculations

Abstract: The adsorptive interactions of 2-propanol (2-PrOH) molecules with silica surfaces were investigated using ab initio and density functional calculations. Two cluster models of silica were chosen to represent the terminal ≡SiOH groups and the siloxane bridges ≡Si-(O) 2-Si≡ on the silica surface. The Hartree-Fock (HF) and Density Functional Theory (DFT) approaches, employing a 6-31G(d) basis set, were used to calculate the geometries, electronic structures, vibrational frequencies and adsorption energies of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, it is determined only by the reactivity of the pentanoic acid molecule itself and the coordination capabilities of the silicon atoms on the surface. The formation of such a surface complex was also shown by Abdallah and coauthors . Additionally, the existence of two types of water in the IR spectra until the complete conversion of acid into ketene provides additional evidence of the bonding of acids with strained siloxane bridges …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, it is determined only by the reactivity of the pentanoic acid molecule itself and the coordination capabilities of the silicon atoms on the surface. The formation of such a surface complex was also shown by Abdallah and coauthors . Additionally, the existence of two types of water in the IR spectra until the complete conversion of acid into ketene provides additional evidence of the bonding of acids with strained siloxane bridges …”
Section: Resultssupporting
confidence: 61%
“…The formation of such a surface complex was also shown by Abdallah and coauthors. 55 Additionally, the existence of two types of water in the IR spectra until the complete conversion of acid into ketene provides additional evidence of the bonding of acids with strained siloxane bridges. 44 Figure 8 schematically shows all types of adsorption complexes obtained as a result of DFT modeling.…”
Section: In Situ Ir Study Of Valeric Acid Conversion Over Silica Obta...mentioning
confidence: 99%
“…This is further supported by apparent activation enthalpies (6.3 kcal mol À 1 for batch reactor [11b] vs 14.0 kcal mol À 1 for flow reactor) indicating less contribution of mass transfer and higher contribution of bond-breaking in the β-elimination step in the flow reactor case, and also by a reaction order of one in iridium centers in the flow reactor compared to 0.5 in the batch reactor. Plausibly, support effects, such as differential interaction of the supports with acetone and isopropanol (that are adsorbed) [25][26][27] and hydrogen (that is not adsorbed) [25] may give rise to the observed effects, but further studies are needed to confirm or disprove this hypothesis.…”
Section: Chemsuschemmentioning
confidence: 99%
“…For comparison, Abdallah et al (2009 ) found that, with the same B3LYP/6-31G(d) level of theory, bond lengths for hydrogen bonds were 1.7 Å and 1.9 Å for the physical adsorption of isopropanol on a silica surface. For THF adsorbed on the silica surface, not only the identical bond lengths, but also the localization of the Si–OH proton between the oxygen of the silanol group and the oxygen of the THF ( Figure 9 ) indicate the formation of a hydrogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…As a model system for calculations, a 32 T (tetrahedral) silica cluster (cell size of approximately 1 nm × 1 nm) has been used in its non-hydroxylated and hydroxylated forms (no OH group and 2 OH groups/nm 2 , respectively), which resulted in a Si 32 O 68 H 8 composition (108 atoms as a whole). The SiO 2 cluster model and the adsorption structures of different probe molecules were optimized in the gas phase at the B3LYP/6-31G (d) level of theory, which seems to be a reliable method for studying the structures and stabilities of silica materials ( Abdallah et al, 2009 ; Rimola et al, 2013 ). This computational model has also been successfully used in our previous works ( Bauer et al, 2017 ; Bauer et al 2019 ; Bauer et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%